A Qualitative Study on the Implementation of Character Education in Preventing Bullying - Berkat Iman Jaya Gea; Anugerah Tatema Harefa; Hendrikus Otniel Nasozaro Harefa; Berkat Persada Lase (Jurnal Inovasi, Evaluasi dan Pengembangan Pembelajaran, 2026)
Bullying in junior high schools remains a persistent issue, indicating that character education has not been optimally implemented as a preventive strategy. This study aims to examine the implementation of character education in preventing bullying at SMP Negeri 1 Hiliduho and to identify supporting and inhibiting factors affecting its effectiveness. A qualitative case study approach was used to gain an in-depth understanding of practices within the natural school setting. Data were collected through interviews, observations, and document analysis involving the principal, civics teacher, and vice principal for student affairs. The findings show three main implementation patterns: preventive socialization on bullying awareness, habituation of character values through routine and extracurricular activities, and integration of values such as respect, empathy, and responsibility into classroom learning. The effectiveness of these efforts is supported by strong institutional commitment, collaboration among school members, and a positive school culture. However, several challenges were identified, including limited supervision, inconsistent student behavior, and lack of family support, which may hinder sustainability. These findings indicate that character education in bullying prevention should not be limited to classroom instruction but requires a holistic approach involving school culture, consistent supervision, and collaboration between schools and families. Strengthening systemic support and reinforcing value-based practices are essential to ensure long-term effectiveness.